Faktor Internal dan Eksternal Usaha Minyak Kelapa Mandar Milik Ibu Yanti di Desa Simbang Kecamatan Pamboang Kabupaten Majene - Busman Busman; Syamsul Rahman; Syamsinar Syamsinar,; Helda Ibrahim (CV. Green Publisher Indonesia, 2026)
Background: Indonesia is an agricultural country with superior plantation commodities, one of which is coconut (Cocos nucifera). Majene Regency as one of the coconut centers in West Sulawesi has great potential in the development of derivative products, including Mandar coconut oil. Objective: to analyze the internal and external factors that affect Mandar coconut oil business owned by Mrs. Yanti.Formulate the right business development strategy based on the results of the analysis. Method: this study uses a descriptive qualitative approach with a case study method on coconut oil business owned by Mrs. Yanti in Simbang Village. Data were obtained through observation, in-depth interviews, and documentation. Data analysis was conducted using SWOT analysis through the preparation of IFAS Matrix (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), SWOT Matrix, and Cartesian Diagram to determine the position of business development strategy. Results: the results showed that internally Mandar coconut oil business has strength in the quality of natural products, distinctive aroma, and business experience that has been going on for a long time. However, there are weaknesses in the aspects of capital, production technology, packaging, and marketing are still limited.From the external side, there are opportunities in the form of local market potential, government support for MSMEs, and increased interest in traditional and natural products. On the other hand, the threat comes from the competition of oil mills, fluctuations in prices for raw materials, as well as changes in consumer preferences. Conclusion: based on the SWOT analysis, the recommended business development strategy is to utilize the strengths to face threats (s–T strategy), as well as take advantage of opportunities through improved management quality, packaging innovation, marketing expansion, and more efficient utilization of production technology.